2004
DOI: 10.1289/ehp.7108
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled Breath Condensate as a Suitable Matrix to Assess Lung Dose and Effects in Workers Exposed to Cobalt and Tungsten

Abstract: The aim of the present study was to investigate whether exhaled breath condensate (EBC), a fluid formed by cooling exhaled air, can be used as a suitable matrix to assess target tissue dose and effects of inhaled cobalt and tungsten, using EBC malondialdehyde (MDA) as a biomarker of pulmonary oxidative stress. Thirty-three workers exposed to Co and W in workshops producing either diamond tools or hard-metal mechanical parts participated in this study. Two EBC and urinary samples were collected: one before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 27 publications
1
63
0
Order By: Relevance
“…At this stage, it is only possible to capitalise on studies dealing with EBC analysis in diseased conditions, although in these studies a limited number of healthy subjects matching the characteristics of the diseased group are usually used as a control group. In this context, a number of such publications have dealt with the same mediator, therefore, more data are available in healthy controls (table 6) [77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93]. The only exception is a recent study dealing not with a mediator or chemical compound but with pH values in healthy subjects [87].…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…At this stage, it is only possible to capitalise on studies dealing with EBC analysis in diseased conditions, although in these studies a limited number of healthy subjects matching the characteristics of the diseased group are usually used as a control group. In this context, a number of such publications have dealt with the same mediator, therefore, more data are available in healthy controls (table 6) [77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93]. The only exception is a recent study dealing not with a mediator or chemical compound but with pH values in healthy subjects [87].…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…The field in which EBC analysis may soon have a recognised clinical application is in assessing exposure to chemical compounds potentially harmful to the respiratory system, e.g. in the screening of occupational/environmental risk or toxic effects of a given compound in exposed individuals [91]. This type of ''occupational'' application of EBC analysis to detect a biomarker of exposure/effect is rather analogous to the role of induced sputum in occupational asthma [94], representing an example of how the development of a new biological tool may capitalise on previous experience with other types of sample analysis.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…4) seem to indicate that the BF is a minor excretion route for Hg. We have recently demonstrated that levels of pneumotoxic metals in exhaled breath condensate, sharing some commonality with BF, are promising markers of effective dose at the target organ in exposed workers (59). Different chelating agents, including penicillamine, dimercaprol, 2,3-dimercaptopropane-1-sulphonate (DMPS), and DMSA, have been administered in cases of i.v.…”
Section: Discussionmentioning
confidence: 99%
“…There are no published data concerning the Cr(VI)/Cr(III) equilibrium in the airway lining fluid, nor any data is available concerning its reducing power, although different concentrations of individual reducing agents (glutathione, ascorbic acid) may affect the reduction of Cr(VI) to Cr(III), and thus the levels of Cr(VI) that reach pulmonary tissue [12]. The measurement of Cr(VI) in EBC, which is also a suitable fluid for assessing the lung doses and effects of cobalt and tungsten in exposed workers [13], may therefore be a useful means of following the reduction pathways of Cr at target organ level and studying the mechanisms of pulmonary Cr(VI) toxicity.…”
Section: Introductionmentioning
confidence: 99%